Enhanced thermo-mechanical damage tolerance of functionally graded ZrB2-20SiC ceramic reinforced with carbon nanotubes. Issue 5 (1st April 2019) - Nisar, Ambreen; Khan, Mohammad Mohsin; Balani, Kantesh
Abstract: The demand of a new generation spacecraft component has led to the development of a novel structure, which combines the traits of both functionally graded material (FGM) as well as an ultra-high temperature ceramics (UHTC). Herein, FGM based on the well-established ZrB2 -20SiC (vol%) UHTC with the reinforcement of carbon nanotubes (CNT) is processed via powder metallurgy and spark plasma sintering (SPS). A densely graded microstructure with a crack-free seamless interface is witnessed along the cross-section of the FGM. The CNT in the optimized FGM is found to be efficaciously embedded in the matrix retaining its structure during sintering (at 1850 °C), shown microstructurally and supplemented by Raman spectroscopy. Enhanced mechanical and wear resistance of the FGM when compared to that of the conventional ZrB2 UHTC is attributed to the dense, crack-free microstructure and CNT pull-out mechanism. Oxidation test revealed an enhancement in the thermal stability as the onset of oxide formation starts above 886 °C (i.e. > 30% when compared to that of monolithic ZrB2 ). The thermo-structural performance of the processed FGM simulated using finite element method (FEM) indicated a reduction in the thermal residual tensile stresses (~ 8.1 times) which mitigates the crack propagation. The FEM analysis complements the high indentation fracture toughness values of the FGM even at the interfaces (similar to that found in each layer), establishing FGM approach superior to that of the conventional UHTC composites. Thus, addition of CNT in ZrB2 -20SiC based FGM are conducive enough to be engineered as a potential material, poised to shape the future of re-entry vehicles.